C-Reactive Protein and TGF-α Predict Psychological Distress at Two Years of Follow-Up in Healthy Adolescent Boys: The Fit Futures Study - Linkas, Jonas; Ahmed, Luai Awad; Csifcsak, Gabor; Emaus, Nina; Furberg, Anne-Sofie; Grimnes, Guri; Pettersen, Gunn; Rognmo, Kamilla; Christoffersen, Tore (Frontiers in Psychology, 2022)
Objective: The scarcity of research on associations between inflammatory markers and symptoms of depression and anxiety during adolescence have yielded inconsistent results. Further, not all studies have controlled for potential confounders. We explored the associations between baseline inflammatory markers and psychological distress including moderators at follow-up in a Norwegian adolescent population sample. Methods: Data was derived from 373 girls and 294 boys aged 15-18 years at baseline, in the Fit Futures Study, a large-scale two-year follow-up study on adolescent health. Baseline data was gathered from 2010 to 2011 and follow-up data from 2012 to 2013. Psychological distress was measured with Hopkins Symptom Checklist (HSCL-10). Serum-levels of the following inflammatory markers were measured: C-reactive protein (CRP), Interleukin 6 (IL-6), Transforming growth factor-alpha (TGF-α), Tumor necrosis factor alpha variant 1 (TRANCE) and variant 2 (TWEAK). Independent associations between baseline inflammatory markers and HSCL-10 at follow-up were explored by linear regressions, in sex-stratified analyses. Results: In girls, analyses showed positive associations between all inflammatory markers and HSCL-10, except for TRANCE. However, all associations were non-significant in crude as well as in adjusted analyses. In boys, CRP (p=0.03) and TGF-α (p<0.01) showed significant associations with HSCL-10, that remained significant after adjustment. Additionally, moderators were found. In boys, CRP was associated with HSCL-10 in those with high body fat and those being physical inactive, and the association between TWEAK and HSCL-10 was dependent upon sleep duration. Conclusion: There was significant prospective associations between CRP, TFG-α, and HSCL-10 in boys aged 15-18 years at baseline.